(untitled) (Research, Society and Development, 2020)
The present study addressed a cinematic analysis of the movie "The Lighthouse of the Orcas". Through the look of Psychology, the activity is the result of a practical application of the contents seen at the discipline of Basic Processes. The aim of this paper was to present a case study from the view of Cognitive Psychology, by analyzing the behavior of the main character of the film. Through the analysis of scenes from the movie, it was possible to investigate specifically how the character’s displacements are associated with the basic cognitive processes such as memory, learning, perception, attention and language. The results of the analysis indicate that the patient Tristán, from the point of view of cognitive psychology, presented alterations in his cognitive functions. Thus, through film analysis it was possible to associate the behavior of the character from the movie The Lighthouse of the Orcas to the subject learned in the discipline of Basic Processes. This activity, although through a fictional perspective, allowed the observation of characteristic aspects and symptoms of the mental disorder presented in the film based on the perspective of Cognitive Psychology.